Effects of Sub-acute Ethanol Extract Toxicity of Karamunting (Rhodomyrtus tomentosa) Leaves on Hematological Profile in Female White Rats - Tia Wida Ekaputri; Hana Nurul Qur’ani; Citra Maharani; Anggelia Puspasari; Budi Justitia; Esa Indah Ayudia; Fitriyanti (Journal of Medical Studies, 2024)
ABSTRACT Background: Karamunting leaves (Rhodomyrtus tomentosa) are a medicinal plant widely used in Indonesia for their bioactive compounds, which exhibit anti-inflammatory, antibacterial, antioxidant, antidyslipidemic, and anti-hyperglycemic properties. However, the safe dosage for human use remains undetermined. This study aims to assess the sub-acute toxicity of ethanol extracts of karamunting leaves on the hematological profile of female white rats. Methods: This study used an experimental laboratory design with a post-test control group. Karamunting leaves were extracted by maceration using 70% ethanol as the solvent. The hematological profiles measured included erythrocytes, leukocytes, platelets, and hematocrit levels. Female white rats of the Wistar were randomly divided into six groups. The negative control group received only a 0.5% Na CMC suspension, while the treatment groups received ethanol extracts of karamunting leaves at doses of 200 mg/kg BW, 400 mg/kg BW, 800 mg/kg BW, 1600 mg/kg BW, and 3200 mg/kg BW. Blood samples were collected after 14 days of treatment. Results: The hematological profiles indicated no significant differences among the groups. However, the treatment group that received extracts at a dose of 1600 mg/kg BW showed a poor hematological profile. Conclusion: Generally, the ethanol extract of karamunting leaves did not affect the hematological profiles of the test animals. Keywords: Rhodomyrtus tomentosa; hematological profile; sub-acute toxicity